Conic Optimization, with Applications to (Robust) Truss Topology Design - C. Roos; D. Chaerani (Institute for Research and Community Services (LPPM) ITB, 2002)
After a brief introduction to the field of Conic Optimization we presentsome interesting applications to the (robust) trus topologr design (TTD)problem, where the goal is to design a truss of a given weight best ableto withstand a set of given loads. We present a linear model for thesingle-load case and semidefinite models for the multi-load and the ro'bust TTD problem. All models are illustrated by examples. It is alsoshown that by using duality the size of some of these models can bereduced significantly.